ERDVĖS IR LAIKO SAMPRATOS UGDYMO FILOSOFIJOJE: NUO MOKSLINĖS PEDAGOGIKOS PRIE KASDIENĖS PRAKTIKOS. - Duoblienė, Lilija (Problems / Problemos, 2013)
The article analyses the understanding of the concepts of time and space as structures of contemporary social and personal life and how these concepts are applied in education. Tthe starting point for the investigation of the definitions of time and space lies in Michel Foucault's theory about disciplining of society and repressive pedagogy, which was later developed by Michel de Certeau, Gilles Deleuze, Maarten Simons, Jan Masschelein. While Simons and Masschelein continue to develop the idea of social disciplining through the new modern practices, de Certeau and Deleuze give alternative interpretations of how to escape social manipulations and limitations of personal life. De Certeau explains the transformations of time and space structures from the perspective of mapping individual trajectory. Deleuze pays more attention to the variety of possibilities in the process of creative encountering and space-shifting through an event. The analysis of the concepts of time and space enables an explanation of modernization of repressive contemporary education and allows turning from the critical point of view towards creative approach to education.